AJRAVS 2018
DOI: 10.9734/ajravs/2018/45334
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology and Seasonal Hematological Parameters in Tegu Lizards (Salvator merianae) Raised in Captivity

Silvia N. Chamut,
Osvaldo E. A. Arce

Abstract: This work was carried out in collaboration between both authors. Author SNC designed the study, wrote the protocol, did the experimental work and the data collection and wrote the draft of the manuscript. Author OEAA performed the statistical analysis, managed the analyses of the study and collaborated in the writing of the final version of the manuscript. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 19 publications
(33 reference statements)
16
5
0
Order By: Relevance
“…Frontiers in Veterinary Science 07 frontiersin.org individualized cells in tegu 2. Individual thrombocytes measured ~6-8 μm and had a scant amount of clear-to-faint blue cytoplasm and ovoid nuclei containing condensed chromatin, which is similar to that previously reported in Romanowsky-based stain (6). Thrombocytes were only positive for PAS in both tegus (Figure 2; Table 1), with staining on the edges of the cytoplasm in the individual cells in tegu 2.…”
Section: Thrombocytessupporting
confidence: 81%
See 2 more Smart Citations
“…Frontiers in Veterinary Science 07 frontiersin.org individualized cells in tegu 2. Individual thrombocytes measured ~6-8 μm and had a scant amount of clear-to-faint blue cytoplasm and ovoid nuclei containing condensed chromatin, which is similar to that previously reported in Romanowsky-based stain (6). Thrombocytes were only positive for PAS in both tegus (Figure 2; Table 1), with staining on the edges of the cytoplasm in the individual cells in tegu 2.…”
Section: Thrombocytessupporting
confidence: 81%
“…Previous publications have reported that eosinophils in the Argentine black and white tegu are indistinguishable from heterophils with the May-Grűnwald-Giemsa stain (6)(7)(8). Monocytes in this species are described as containing an electron-lucent variably shaped inclusion (6), while another report describes WBCs containing oval to linear cytoplasmic clearings of unknown origin in an apparently healthy red tegu (Salvator rufescens) and a Savannah monitor (Varanus exanthematicus) (3), which is from a different taxonomic family (Varanidae). The objective of this study was to perform a suite of cytochemical staining and transmission electron microscopy (TEM) on blood submitted for a complete blood count (CBC) from one Argentine black and white tegu to identify the cellular origin of the WBC with the previously described inclusion/cytoplasmic clearing that has been a mystery to date.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous publications have reported that eosinophils in the Argentine black and white tegu are indistinguishable from heterophils with the May-Grűnwald-Giemsa stain (6)(7)(8). Monocytes in this species are described as containing an electron-lucent variably shaped inclusion (6), while another report describes WBCs containing oval to linear cytoplasmic clearings of unknown origin in an apparently healthy red tegu (Salvator rufescens) and a Savannah monitor (Varanus exanthematicus) (3), which is from a different taxonomic family (Varanidae). The objective of this study was to perform a suite of cytochemical staining and transmission electron microscopy (TEM) on blood submitted for a complete blood count (CBC) from one Argentine black and white tegu to identify the cellular origin of the WBC with the previously described inclusion/cytoplasmic clearing that has been a mystery to date.…”
Section: Introductionmentioning
confidence: 94%
“…They are common in the international live animal trade as pets, are an established invasive species in Florida and Georgia in the United States, and are hunted for their skins in various South American countries (4). Previous publications have reported that eosinophils in the Argentine black and white tegu are indistinguishable from heterophils with the May-Grűnwald-Giemsa stain (6)(7)(8). Monocytes in this species are described as containing an electron-lucent variably shaped inclusion (6), while another report describes WBCs containing oval to linear cytoplasmic clearings of unknown origin in an apparently healthy red tegu (Salvator rufescens) and a Savannah monitor (Varanus exanthematicus) (3), which is from a different taxonomic family (Varanidae).…”
Section: Introductionmentioning
confidence: 99%